Transcendental a priori and conventional a priori. The devious path of apriority from Kant to Putnam - Melogno, Pablo (Analysis. Journal of Philosophical Research, 2018)
In several works produced in the 60’s and 70’s, Putnam introduced the notion of contextually a priori, trying to give an account of the principles that fix the limits of the possible experience within a conceptual scheme. According to Putnam, these principles are originated by the satisfaction of specific cognitive needs, and not by conventional stipulations. This paper discusses the putnamian notion of the a priori in relation to the stances of Poincaré, Reichenbach and Carnap, trying to establish in each case the points of convergence with the putnamian conception, as well as the reasons that led Putnam to reject the conventionalist views of the a priori. It is argued that the putnamian account can be considered as a rehabilitation of the transcendental component of the Kantian a priori, as for Putnam the a priori principles are not only constitutive of the objects, but they fix cognitive limits that can only be overcome in contexts of conceptual change.